2011
DOI: 10.1074/jbc.m111.251330
|View full text |Cite
|
Sign up to set email alerts
|

C-terminal Domain of Chromogranin B Regulates Intracellular Calcium Signaling

Abstract: Background: Chromogranin B (CGB) is a buffer for calcium and a functional binding partner of the inositol 1,4,5-trisphosphate receptor (InsP 3 R). Results: The domains of CGB differentially regulate initiation and duration of intracellular calcium signaling. Conclusion: C-CGB activates intracellular calcium signaling and N-CGB binds to InsP 3 Rs. Significance: This study demonstrates the importance of CGB in the modulation of InsP3Rs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…Our study demonstrates that in symptomatic EAE mice, a dramatic accumulation of CGB occurs. This increase in CGB likely contributes to the elevation of cytosolic calcium levels, as demonstrated by prior studies (Choe et al, 2004; Jacob et al, 2005; Schmidt et al, 2011). The elevation in cytosolic calcium then turns on calcium dependent proteases, namely, calpain.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…Our study demonstrates that in symptomatic EAE mice, a dramatic accumulation of CGB occurs. This increase in CGB likely contributes to the elevation of cytosolic calcium levels, as demonstrated by prior studies (Choe et al, 2004; Jacob et al, 2005; Schmidt et al, 2011). The elevation in cytosolic calcium then turns on calcium dependent proteases, namely, calpain.…”
Section: Discussionsupporting
confidence: 60%
“…It was previously found that in areas with little InsP3R, CGB levels are elevated to compensate for the decreased InsP3R expression (Nicolay et al, 2007). Additionally, subcellular changes in intracellular CGB expression lead to significantly altered calcium release kinetics and calcium signal initiation sites (Choe et al, 2004; Jacob et al, 2005; Schmidt et al, 2011). For instance, overexpression of CGB causes an increase in InsP3R mediated-calcium release.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, three studies tried to investigate the potential role of the polymorphism c.1238CNT in exon 4 of the CHGB gene in different ALS populations Van Vught et al, 2010;Blasco et al, 2011). This SNP is located in the C-terminal region of CgB, crucial for inducing calcium release (Schmidt et al, 2011), but not within or in proximity of the known binding site to mutant SOD1, located in a Hsp-like domain (region 162-285) . Moreover, the region containing the variation has not been conserved during evolution , suggesting that the functional role for this region could be limited.…”
Section: Discussionmentioning
confidence: 99%